2021
DOI: 10.1038/s41598-021-91857-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of significantly high vitreous concentrations of fatty acid-binding protein 4 in patients with proliferative diabetic retinopathy

Abstract: The fatty acid-binding protein4 (FABP4) and vascular endothelial growth factor A (VEGFA) play key roles in the metabolic and cardiovascular diseases, and proliferative diabetic retinopathy (PDR), respectively. To identify FABP4 in vitreous fluid in PDR, vitreous concentrations of FABP4 (V-FABP4) and VEGFA (V-VEGFA) from PDR (n = 20) and non-PDR (n = 20) patients were determined by Enzyme-Linked ImmunoSorbent Assays. The data, which included height and weight, systemic blood pressures, several blood biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Furthermore, this follow-up study ultimately revealed the role of FABP4 as an independent prognostic biomarker of DR or VTDR in diabetic patients. Interestingly, Itoh et al [ 9 ] confirmed the existence of FABP4 in the vitreous fluid of PDR patients and found that the vitreous concentration of FABP4 was significantly higher in PDR patients than in non‐PDR patients. These observations strongly suggest that FABP4 may play a partial role in the pathogenesis of DR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this follow-up study ultimately revealed the role of FABP4 as an independent prognostic biomarker of DR or VTDR in diabetic patients. Interestingly, Itoh et al [ 9 ] confirmed the existence of FABP4 in the vitreous fluid of PDR patients and found that the vitreous concentration of FABP4 was significantly higher in PDR patients than in non‐PDR patients. These observations strongly suggest that FABP4 may play a partial role in the pathogenesis of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid-binding protein 4 (FABP4) is abundantly expressed in adipocytes, capillary endothelial cells (ECs), and macrophages [ 8 ]. It exists in most bodily fluids [ 9 ]. The role of FABP4 was raised for the first time by Xu et al [ 10 ], and numerous studies have demonstrated that FABP4 plays a crucial role in fatty acid delivery and utilization, cell proliferation and differentiation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quite interestingly, we found that the levels of FABP4 and VEGFA were elevated in patients with RVD as compared to the corresponding values for non-RVD controls and substantial and that there was a positive correlation between them [22,23]. Furthermore, the correlation of both factors with several clinical parameters, and stepwise multivariable regression analyses strongly suggested that vitreous FABP4 (V-FABP4) and vitreous VEGFA (V-VEGFA) may independently be involved in the pathogenesis of RVD [22,23]. These collective findings prompted us to investigate the roles of several FABP isoforms within the eye in several animal models with retinal diseases, in addition to human eyes.…”
Section: Introductionmentioning
confidence: 72%
“…To examine this possibility further, we recently measured the vitreous levels of FABP4 and vascular endothelial growth factor A (VEGFA), which is recognized as an established therapeutic target [20,21], in patients with RVD. Quite interestingly, we found that the levels of FABP4 and VEGFA were elevated in patients with RVD as compared to the corresponding values for non-RVD controls and substantial and that there was a positive correlation between them [22,23]. Furthermore, the correlation of both factors with several clinical parameters, and stepwise multivariable regression analyses strongly suggested that vitreous FABP4 (V-FABP4) and vitreous VEGFA (V-VEGFA) may independently be involved in the pathogenesis of RVD [22,23].…”
Section: Introductionmentioning
confidence: 74%
“…Notably, FABP4 is highly expressed in diabetic complications, such as diabetic nephropathy and gestational diabetes, and inhibition of FABP4 not only ameliorates high glucose-induced glomerular cell apoptosis by regulating endoplasmic reticulum stress, but also increases serum insulin concentrations and reduces pancreatic inflammation, thereby alleviating the progression of these diseases [ 5 , 6 ], suggesting that FABP4 is involved in and regulates the development of diabetes-related diseases. Recent clinical studies have found that serum FABP4 is positively correlated with the severity of DR and that FABP4 can be used as an independent prognostic marker in patients with type 2 diabetic retinopathy [ 7 , 8 ]. In addition, FABP4 also shows abnormally high expression in retinopathy, and FABP4 deficiency improves pathological retinal vascularization and provides some protection against retinopathy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%